EMPLOYING THE EXPRESSIVIST PEDAGOGY IN WRITING II CLASS - Esti Ambaratsari (Universitas Bengkulu, 2016)
The first main assignment required in the first six weeks of Writing II class was designed on the expressivist approach. The article provides an actual class realization when the assignment was given to a group of forty English Study Programme students, Faculty of Teacher Training and Education, Universitas Bengkulu. Those six weeks were a mixture of hard work, complaint, excitement, and actual texts produced. An overview of the theoretical basis on which the assignment was built is provided followed by a quick account of how the class was conducted employing expressivist pedagogy. At the end of the sixth week, students were asked to write a one-page journal entry to reflect on and evaluate their writing experience. The article tries to analyze this journal entry to uncover what students learned from doing the assignment and how they evaluated their learning. Analysis reveals that students achieved first hand knowledge of the writing process and the requirements needed to develop readable effective texts.